SWOT ANALYSIS IN THE MARKETING STRATEGY OF THE EDUCATIONAL TOURISM VILLAGE DURING PANDEMIC COVID-19 - Dharma, Buyung Adi; Mukhlis, Imam; Zagladi, Arief Noviarakhman (International Journal of Business, Law, and Education, 2023)
The purpose of this study was to determine the right strategy for marketing the educational tourism village in Kampung inggris Pare. Data analysis in this study used descriptive qualitative methods with case studies. Data sources were obtained from observation, interviews with 5 informants from Kampung Inggris Pare, and documentation in the form of photos and voice recordings. Checking the validity of the data using triangulation of sources and triangulation techniques. This research resulted in 3 conclusions, including: (1) Strengths for Kampung Inggris Pare: (1) The strengths of Kampung Inggris Pare consist of the low cost of living, comfortable learning atmosphere equipped with facilities from the institution, and health insurance for all elements of Kampung Inggris Pare. Then some weaknesses of Kampung Inggris Pare include the tight learning hours, less maintained environment at some points, and less efficient access to Kampung Inggris Pare. (2) The most potential opportunities for Kampung Inggris Pare include the number of fresh graduates, the recommendation of Kampung Inggris Pare alumni, and the potential arrival of students as a result of extensive promotion. As well as threats that can have an impact on Kampung Inggris Pare consist as the ongoing COVID-19 pandemic, the existence of restrictions by the government, and the lack of holiday time for prospective students of Kampung Inggris Pare. (3) The strategic position based on the SWOT Diagram is in quadrant 1, which means that Kampung Inggris Pare can use an aggressive strategy with the results of the SWOT Matrix in the SO (Strengths-Opportunity) position. These strategies include utilizing alumni in promotional media by displaying the advantages of Kampung Inggris Pare, adding vaccination activities and health facilities, as well as promotions in the form of discounts and free products for fresh graduates who come to Kampung Inggris Pare